EVALUATION OF BISPECTRAL INDEX GUIDED TARGET-CONTROLLED INFUSION PROPOFOL ANESTHESIA IN PATIENTS RECEIVING HIGH-FLOW NASAL OXYGEN DURING APNEA FOR ENDOSCOPIC VOCAL CORD SURGERY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness and safety of bispectral index (BIS)–guided target-controlled infusion (TCI) propofol anesthesia in patients receiving high-flow nasal oxygen during apnea in endoscopic vocal cord surgery. Methods: A prospective descriptive study was conducted on 130 patients undergoing endoscopic vocal cord surgery at 108 Military Central Hospital from October 2022 to December 2025. General anesthesia was induced and maintained using TCI propofol combined with rocuronium for neuromuscular blockade. BIS values, hemodynamic and respiratory parameters, recovery time, and adverse events were recorded and analyzed. Results: The mean duration of anesthesia was 30.06 ± 2.03 minutes, and the mean total propofol dose was 330.9 ± 18.2 mg. The mean recovery time was 4.80 ± 1.20 minutes. Hemodynamic parameters and oxygen saturation remained stable throughout the procedure. No serious respiratory or cardiovascular adverse events were observed. Conclusion: BIS-guided TCI propofol anesthesia combined with high-flow nasal oxygen during apnea is effective and providing rapid recovery. No serious adverse events on respiration and circulation have been recorded.
Keywords: Endoscopic vocal cord surgery, high-flow nasal oxygen, propofol, bispectral index.